Accounting Information System for Sales of Oil Palm Seeds at Pt. Socfindo - Riswan Ober Bornok Manurung (Journal of Computer Science and Research (JoCoSiR), 2023)
The development of sophisticated science and technology is now felt by users of a computer-based information technology. With today's technological sophistication, every company and public service agency is required so that all work can be completed in a computerized system. PT. Socfindo Medan is a company engaged in agriculture. Problem formulation at PT. Socfindo is not yet created a computerized system in conducting sales transactions so that work is still less effective and efficient. To overcome the problems that exist in PT. Socfindo the author wishes to create a new information system. To create an information system the author uses the VB.Net programming language with SQL Server Database. The purpose of making this system is to facilitate the transaction and sales data processing. The reports generated are also more accurate.